Assessing preservice teachers’ knowledge of the relationship between perimeter and area - Thiam Yew, W. (2014)
This paper attempts to assess preservice teachers’ knowledge of the relationship between perimeter and area. In this study, the researchers employed survey research design to assess preservice teachers’ knowledge of the relationship between perimeter and area. A questionnaire was employed to collect the data. Convenient sampling technique was employed to select the participants of the study. Respondents of the study consisted of 34 preservice teachers (majored or minored in mathematics) who are attending Bachelor of Science with Education program at a public university in Peninsula Malaysia. This paper presents the analysis of the responses of the preservice teachers related to a particular mathematical task, namely Same perimeter, same area? The finding suggests that 73.53% of the preservice teachers in this study provided the correct response that the student’s method of calculating the area of the leaf was not correct. They knew that there is no direct relationship between perimeter and area. The preservice teachers knew that two shapes with the same perimeter can have different areas. Thus, they knew that the student’s method of calculating the area of the leaf was not correct. Implications of the findings were also discussed.